Comparative seismic RISK assessment of existing RC buildings using seismic vulnerability index approach. (August 2021) - Kassem, Moustafa Moufid; Mohamed Nazri, Fadzli; Noroozinejad Farsangi, Ehsan; Tan, Chee Ghuan
Abstract: The implementation of seismic risk management is becoming increasingly important all over the world, and especially in East-Asia as the structures aging surpass. In this context, three existing reinforced concrete buildings located in Malaysia have been selected for seismic vulnerability assessment. This work aims to apply the Seismic Vulnerability Index (SVI) via a Non-Linear Parametric Analysis (NL-PA) for each of the 3 RC existing buildings having different storey levels and clusters; low-rise (BLR), mid-rise (BMR), and high-rise (BHR). This approach can be achieved by undertaking a NL-PA as an analytical strategy instead of the empirical approach, which relies primarily on physical vulnerability parameters, earthquake-resistant design (ERD), and engineering demand parameters (EDP) by simulating a set of seismic records that can define the fragility features. The assessed SVI values for three different clusters of buildings are obtained for Far-Field (FF) and Near-Field (NF) seismic scenarios. With regards to the non-linear static analysis (NL-SA), the SVI values interact very well with the findings acquired from the NL-DA which are in good compliance with the low-rise building, in contrast for the two mid- and high-rise buildings. According to the obtained probabilistic vulnerability curves, the reference buildings are classified to be in D2 and D3 damage grades with dominancy of D3 level for the mid-rise and high-rise structures.